Kekuatan Pembuktian Akta Notaris yang Mengandung Kesalahan dalam Penulisan Komparisi - Budiawan Budiawan (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
Improvements in "comparition" writing errors (the act of present in the public officials) shall be in accordance with the procedures under applicable laws, since essentially what is contained in the authentic deed must be true, so that the authenticity of the Deed is evident can be maintained. This is the duty of the Notary, because he must ensure that documents of the constraints such as the identity and the evidence are true. The end of this paper concludes that (1) the composition of the deed is not in accordance with the provisions imposed by the law regulating the category of a violation, and (2) the civil notary liability on the deed made, in this case the responsibility to the material truth of the deed, in the construction of the act against the law, so that if from the mistake material or material damage occurs then the notary is obliged to repair or replace the loss.